Effect of macroscopic stress, cold work and microstructure on the resistivity and hall coefficient in NI based superalloys - Shao, Zhaoyu (Nanyang Technological University, 2020)
The knowledge of residual stress profile generated by subsurface processes in aircraft turbine engine components enables more reliable prediction of the remaining life. Unfortunately the existing mature techniques, e.g. X-ray diffraction (penetration depth < 20 μm) and hole drilling, are destructive and therefore expensive for these routinely inspected components. The objective of this work is to demonstrate the feasibility of two electromagnetic techniques for non-destructive residual stress assessment of aircraft turbine engine components undergone subsurface processes. According to a detailed review of the existing non-destructive residual stress measurement techniques including diffraction, ultrasonic, magnetic and electromagnetic, thermal techniques, Hall coefficient method is anticipated to be promising and targeted for further investigations. Experimental setup has been established for Hall coefficient measurements. The best precision achieved by the Hall coefficient measurement system is better than 0.1%. The temperature effect on Hall coefficient has been quantified in two nickel-base superalloys and the linear relationship facilitates temperature compensation of future measurements. This system can also be used for Alternating Current Potential Drop (ACPD) resistivity measurements with minor modifications and this may enable another approach for residual stress assessment based on the piezo-resistive effect. The achieved resistivity measurement precision is better than 0.01%. Repeatable linear relationship between resistivity and stress is observed in two orthogonal directions that differed by approximately a Poisson’s ratio for the three types of nickel-base superalloys IN100, RR1000 and IN718. The linear stress dependence of Hall coefficient is first observed qualitatively by the ACPD measurement configuration and later quantified by the Van der Pauw measurement configuration. The linear stress dependence of resistivity and Hall coefficient indicates the great potential of stress/residual stress measurement by these two methods. The cold work effect and microstructure effect on resistivity (conductivity) and Hall coefficient have been investigated quantitatively so that the residual stress assessment can be more reliable by these two non-destructive techniques. It has been found that the cold work effect on either resistivity or Hall coefficient does not exhibit directionality as stress. The cold work effect on resistivity is cancelling the compressive stress effect in RR1000 and IN718 which is detrimental in residual stress assessment of surface enhanced specimens where the compressive residual stress coexists with the cold work. However this method can still be applied for residual stress assessment in specimens without the coexistence of cold work. The cold effect on Hall coefficient is in the same direction as the compressive stress effect for RR1000 and IN718 and therefore separable through appropriate calibrations. Hall coefficient technique is the only known technique that is promising in residual stress assessment of surface enhanced aircraft turbine engine components. Gradual increase in the conductivity and absolute value of Hall coefficient is observed for nickel-base superalloys IN100 and RR1000 with the increase in the aging time. The conductivity and the absolute value of Hall coefficient both increase with the increase in the volume fraction of γ' precipitates during the aging process. The conductivity and Hall coefficient correlation with the average grain size exhibit an opposite trend which is reasonable considering the relationship between the volume fraction of γ' precipitates and the average grain size of γ matrix. The established correlations of microstructure parameters with conductivity and Hall coefficient can be further exploited as a non-destructive method for microstructure or heat treatment characterizations in the future which would results in better lifetime prediction for aircraft engine components.